PENGARUH DIVERSITAS PENGURUS PADA LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN SEKTOR KEUANGAN - Rahindayati, Ni Made; Ramantha, I Wayan; Rasmini, Ni Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.05.TAHUN 2015, 2015)
This study aimed to determine the effect of board diversity consisting of gender diversity, nationality diversity, educational diversity and proportion of outsider directors in broad disclosure of Corporate Social Responsibility (CSR). Results of previous studies show that the gender diversity, nationality diversity, educational diversity and proportion of outsider directors related to disclosure (Permatasari, 2009; Nalikha 2009; Rovers, 2010; Yuniasih et al, 2011). Used an external secondary data in the form of financial statements and annual reports financial sector companies listed in Indonesia Stock Exchange in 2008 -2012. The selection of the sample was based on the purposive sampling method and acquired 52 companies as samples with the number of observations as much as 204. The data analysis technique used is multiple linear regression analysis. The results are variable gender diversity, diversity of nationality, educational diversity and proportion of outsider directors have a positive effect on the CSR disclosure.
Keywords: gender diversity; diversity of nationality; educational diversity and proportion of outsider directors; CSR disclosure